Community energy schemes: the role of public participation and engagement - Kiamba, Lorna; Rodrigues, Lucélia Taranto; Marsh, Julian (2017)
Faced by global challenges brought on by climate-change and over-reliance on fossil fuels, more people are looking towards developing energy systems characterised by renewables. Community energy groups have been identified as key stakeholders who could play a strategic role in enabling the transition to a clean and affordable energy supply. Acting as a contact for local energy consumers they can help residents engage with energy matters by harnessing local natural resources to build social capital, creating revenue to address community needs and combating fuel poverty. As these groups are defined by the communities in which they exist, public participation and engagement is vital to their success. The extent of community involvement could include identifying needs, generating solutions, seeking funding and managing assets to enable positive socio-economic impacts. In this paper, the authors examine how a community energy group in Nottingham adopted a model of local energy generation and storage to improve their energy security and to reduce fuel poverty. Results indicate that the use of various engagement strategies provides opportunities to encourage active discussions, explain processes and gather feedback. The regular planning of these sessions helps to maintain momentum, enthusiasm and commitment and encourage wider participation as the project progresses.